Food engineering handbook : food engineering fundamentals - Varzakas, Theodoros, 1969-; Tzia, Kōnstantina (CRC Press, Taylor & Francis Group, 2015)
"This book provides an up-to-date review of food processing and engineering phenomena. It addresses the basic principles of food engineering technologies used in food processing operations around the world, combining theory with a practical hands-on approach. The book explores the basic and applied aspects of food engineering from mass transfer and heat transfer to steam and boilers, heat exchangers, fluid flow, and novel food processes such as membrane technology. It describes the physico-chemical and microbiological methods for each preservation methodology and addresses interactions between different food constituents"--Resumé vydavatele
Část textu tištěna napříč
Keywords: potravinářství; potravinářská technologie; potravinářská biochemie; food industry and trade; food technology; food biochemistry; příručky; handbooks, manuals, etc